Behavior of bimetallic PtSn/Al2O3 catalysts prepared by controlled surface reactions in the selective dehydrogenation of butane - Bocanegra, Sonia Alejandra (2009)
The "one-pot" circulation reactor system was used for the modification of Pt/Al2O3 catalyst using Controlled Surface Reactions (CSRs) with the involvement of tetraethyltin. At 40 °C the tin anchoring reaction resulted in exclusive formation of alloy type Pt-Sn/Al2O3 catalyst, while at higher temperatures tin was also introduced onto the alumina support. The bimetallic catalysts were characterized by Temperature Programmed Reduction (TPR), H2 and CO chemisorption, XPS and test reactions of the metallic phase (cyclohexane dehydrogenation and cyclopentane hydrogenolysis). It has been demonstrated that the decomposition of surface organometallic species of Sn in the presence of oxygen leads to the formation of Lewis-acid type active sites in the close vicinity of platinum. The formation Sn-Pt alloy phase together with oxidized Sn species has been evidenced by methods of characterization applied. The presence of these species in Pt-Sn/Al2O3 catalysts favors the catalytic behavior in n-butane dehydrogenation, thus increasing the n-butane conversion and the selectivity to olefins, and decreasing the coke deposition.